THE APPLICATION OF ACCOUNTING INFORMATION SYSTEM: REVENUE CYCLE AT PT SILOAM INTERNATIONAL HOSPITALS - MANADO - Marginia Witjahjono; Jantje Tinangon; Steven Tangkuman (Universitas Sam Ratulangi, 2023)
This study aims to describe and design a flow chart for the application of accounting information systems, especially in the revenue cycle, a case study at PT Siloam International Hospitals – Manado. This study used the snowball sampling method which is a sampling technique by conducting informal interviews so that the information needed by the author can be met. The procedures related to data collection are informal interviews and direct observation of hospital business processes. From the results of data collection, the entire process in the accounting information system specifically for the revenue cycle at PT Siloam International Hospitals – Manado is described descriptively and then presented in the form of a flow chart. The comparison of theory and practice that occurs. Based on the results of research conducted on the Application of Accounting Information System: Revenue Cycle at PT Siloam International Hospitals – Manado that some have been carried out to meet operational standards and accounting information system theory, but there are several things that need to be re-evaluated regarding the separation of responsibilities and the provision of more adequate archival document storage.